2021
DOI: 10.1021/acsami.1c14900
|View full text |Cite
|
Sign up to set email alerts
|

l-Cysteine-Modified Graphene Oxide-Based Membrane for Chiral Selective Separation

Abstract: A novel chiral separation membrane was fabricated by assembling l-cysteine (l-Cys)-modified graphene oxide sheets. l-Cys modification leads to an enantiomer separation membrane with an accessible interlayer spacing of 8 Å, which allows high solvent permeability. In the racemate separation experiments under isobaric conditions, the enantiomeric excess (ee) values of alanine (Ala), threonine (Thr), tyrosine (Tyr), and penicillamine (Pen) racemates in the permeation solution were 43.60, 44.11, 27.43, and 46.44%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Compared to conventional polymer membranes, carbon-based materials have exceptional atomic thickness, lamellar 2D structure, high thermal and chemical stability, antifouling property, and high tensile strength for better chiral separation performance . Most carbon materials work as the achiral supporting membrane, especially GO and rGO, and the abundant functional groups can be modified with chiral selectors, such as CDs, chiral amino acids, peptides, and other chiral compounds. Ethylenediamine-β-CD modified GO membrane exhibited extraordinary enantioselectivity with high percent e.e.…”
Section: Membrane Separationmentioning
confidence: 99%
“…Compared to conventional polymer membranes, carbon-based materials have exceptional atomic thickness, lamellar 2D structure, high thermal and chemical stability, antifouling property, and high tensile strength for better chiral separation performance . Most carbon materials work as the achiral supporting membrane, especially GO and rGO, and the abundant functional groups can be modified with chiral selectors, such as CDs, chiral amino acids, peptides, and other chiral compounds. Ethylenediamine-β-CD modified GO membrane exhibited extraordinary enantioselectivity with high percent e.e.…”
Section: Membrane Separationmentioning
confidence: 99%
“…The implementation of elements of chirality, for example, in GO derivatives would represent a fine tuning of the above-described properties for the stereoselective detection and removal of chiral noxious wastes. The chiral functionalisation of GO surfaces has been reported, mainly through bonds with amino acid derivatives [ 93 , 94 , 95 ]. Although both non-covalent and covalent porphyrin-GO conjugates are widely reported [ 96 ], mostly for photovoltaic [ 97 ] or cancer treatment [ 98 , 99 , 100 , 101 ], none of which involve strictu sensu chiral porphyrins, except for the presence of a coordinated chiral group to the central metal ion [ 102 , 103 ].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…[ 10b,14 ] Fortunately, we have demonstrated that PG selectively adsorbs D 2 O molecules, but PG with the loose and porous structure alone has poor membrane‐forming properties, and it is found that the penetration rate of water through PG membrane is too fast to achieve an effective separation time of H 2 O and D 2 O. Therefore, GO membrane with stable structure [ 15 ] is constructed on the top and bottom sides of PG membrane for preparing a GO/PG/GO membrane with macroscopic heterostructure. The membrane not only exhibits excellent mechanical properties, but also the regulation of the thickness ratio of the GO and PG layer can be used for adjusting the balance of permeability and selectivity of the membrane, thereby realizing the efficient and selective separation of D 2 O molecules from natural water.…”
Section: Introductionmentioning
confidence: 99%